Coal Trade Prospects in Selected Countries in East and Southeast Asia Around the Year 2000. - Puno, Recto H.
Countries in East and Southeast Asia feel the need of resorting back to coal as a major source of energy. Most of the projected requirements would have to be imported from outside the region which would entail a tremendous amount by the year 2000. But economies of scale in ocean shipping exist and a substantial reduction of cost can be achieved using bigger vessels. This paper looks into the possibility that economies of scale could justify construction of one or more trans-shipment depots in the region at which large loads from the supply sources are broken up and re-distributed in small vessels to small consumers.